Aplikasi Virtual Driver NDIS (Network Device Interface Specification) untuk Pengembangan Network Analyzer - Sujoko Sumaryono (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
The network analyzer instruments are needed for monitoring, and fault identificationsin a local network. An application program in PC based can realize this instrument. Theinformation MAC (Medium Access Control) frames are needed to develops these applications.In Microsoft Windows environment, there are three methods to capture the MAC frames inthe local network that are direct NIC (Network Interface Controller) chip access, real NICdriver access, and virtual driver NDIS access. Virtual driver NDIS is used in this research,because the methods are independent from kinds of NIC. The result of the research shows: theapplication can to identify MAC address, IP address, protocol transport, services, the packetcontent, and statistically to analyze every packet has passed in the local network. Themonitoring report can be store in a file. The application has successfully analyzed some localnetwork technology, a UTP-Ethernet LAN, a wireless LAN, and a dial-up connection.Keywords: Network analyzer, MAC (Medium Access Control), NIC (Network InterfaceController), and Virtual driver NDIS